Valency and Collocation - Greń, Zbigniew (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article confronts two ways of analysing and interpreting language phenomena: valency studies and collocation studies (on corpus material). The study considers the example of the Czech verb hodit se, which has already been analysed using the tools of valency analysis. The confrontation of the results of the collocate analysis of this verb, confirmed in the corpus material, with its valency structure (including intentions) makes it possible to clarify some aspects of its syntactic and semantic structure.